2010
DOI: 10.1007/s11250-010-9674-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors that determine use of breeding services by smallholder dairy farmers in Central Kenya

Abstract: This study examined the determinants of smallholder dairy farmers' use of breeding services in Nyandarua and Kiambu districts, Central Kenya. Data was collected through semi-structured interviews with 140 randomly selected respondents. The breeding services considered were artificial insemination (AI), natural bull service, or a combination of AI and bull services. A multinomial logit econometric model was used fitting AI as the base category. There was a negative relationship between higher levels of educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 5 publications
1
12
1
Order By: Relevance
“…Moreover, these findings corroborate the observation by Lesorogol (2008) that Kenyan pastoralists derive considerable income from sale of livestock and part of their land, but spend much of it on consumption rather than investment on improving their livestock enterprises. In the case of dairy cattle farmers in high potential areas of Kenya, Murage and Ilatsia (2011) found that agro-ecological zone and access to markets were more important than household income, in influencing farmers' choice of breeding services.…”
Section: Determinants Of Farmers' Choice Of Improved Cattle Breedsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these findings corroborate the observation by Lesorogol (2008) that Kenyan pastoralists derive considerable income from sale of livestock and part of their land, but spend much of it on consumption rather than investment on improving their livestock enterprises. In the case of dairy cattle farmers in high potential areas of Kenya, Murage and Ilatsia (2011) found that agro-ecological zone and access to markets were more important than household income, in influencing farmers' choice of breeding services.…”
Section: Determinants Of Farmers' Choice Of Improved Cattle Breedsmentioning
confidence: 99%
“…However, the major focus of cattle improvement programmes in Kenya has been dairy sub-sector; the beef cattle sub-sector is relatively neglected by policy (Gamba, 2006). Further, there is an extensive literature on adoption of improved cattle breeds by dairy farmers in high potential areas of Kenya (e.g., Tambi, Mukhebi, Maina, & Solomon, 1999;Kavoi et al, 2010;Musalia, Wangia, Shivairo, & Vugutsa, 2010;Murage & Ilatsia, 2011). However, published information on beef cattle farmers' breed choices is very limited (exceptions include Wilson, 2009).…”
mentioning
confidence: 99%
“…As a strategy of maintaining competitive edge in the market, the peri-urban smallholder dairy farmers should establish elaborate governance structures and act collectively in the processing and marketing of milk and milk products, thereby integrating activities vertically and horizontally. However, studies regarding dairy farming in Kenya have focused mainly on productivity, genetics, nutrition and value chain development (Wambugu et al 2011, Kavoi et al 2010Kahi et al, 2004;Gamba, 2006;Mugambi et al, 2014;Murage andIlatsia, 2011 andWambugu, 2000). There are gaps in literature on the determinants of vertical and horizontal integration among smallholder dairy farmers.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in agreement with the conclusions from some studies (Rezvanfar, 2007) which did not show any significant relationship with overall adoption behaviour of AI on dairy farms. Some authors, however, reported a negative correlation between farm size and level of adoption of AI (Murage and Ilatsia, 2011;Devi, 2013). According to Murage and Ilatsia (2011), farmers with smaller hectares tend to adopt AI more as they do not have extra space on which to raise bulls.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors, however, reported a negative correlation between farm size and level of adoption of AI (Murage and Ilatsia, 2011;Devi, 2013). According to Murage and Ilatsia (2011), farmers with smaller hectares tend to adopt AI more as they do not have extra space on which to raise bulls. It is therefore reasonable to find out that farmers in Nyagatare to have adopted IA to the level shown by our results.…”
Section: Discussionmentioning
confidence: 99%